Studi Kasus Asuhan Keperawatan Pada Pasien Post Transurethral Resection Of The Prostate (Turp) Dengan Masalah Risiko Perdarahan Di RSUD Dr. Chasbullah Abdul Madjid Kota Bekasi - Liska Novianty; Rini Nurdini (UP3M AKPER-AKBID BHAKTI HUSADA CIKARANG, 2020)
Background: This scientific paper is motivated by the high numbers that indicate the prevalence ofBPH in 2013 in Indonesia 9.2 million cases of BPH. Whereas in 2019 the incidence of TURP in BPHpatients in Dr. Chasbullah Abdul Majid Regional Hospital in Bekasi City amounted to 56 people inthe period January-May. Bleeding complications can occur, both during and after surgery whichgenerally requires transfusion measures of about 4% of patients undergoing TURP. The author's aimis to gain tangible experience in providing nursing care to post-TURP patients with bleeding riskproblems. TURP is a surgical removal of prostate tissue through the urethra using a resectoscope,after TURP surgery requires CBI (Continuous Bladder Irrigation) monitoring to monitor forbleeding,Research methods: The research method used was a case study, the research subjects used 2 postturp clients with bleeding risk problems, the instruments used were assessment sheets, implementationsheets and evaluations. The analysis technique is used by means of observation by researchers anddocumentation studies that produce data for further interpretation by researchers compared toexisting theories as material to provide recommendations for these interventionsResults: In both patients the risk of bleeding did not occur, all of which occurred in both patientsaccording to the theory.